SLANG AND ITS IMPLICATIONS ON SOCIAL MEDIA - Ignacy, Charles; Kanapathy, Kaaminy (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This paper explores the rapid emergence and widespread use of slang language on social media platforms and its profound implications on communication, education, and cultural identity, with a specific focus on Tamil-English hybrid slang. Slang, often used for quick, expressive, and informal communication among youth, is shown to evolve through digital culture, memes, and cross-language code-switching. While it enhances personal expression and peer bonding, it also poses challenges to traditional grammar, formal writing, and linguistic integrity. The study identifies significant educational concerns such as the decline in formal language proficiency, deviation from curriculum standards, and exclusion of non-native or rural learners. Socially, slang promotes in-group identity and self-branding but can deepen generational and cultural divides. Furthermore, it alters the grammatical and literary aesthetics of Tamil, threatening the sustainability of its classical form. The paper concludes with recommendations for integrating language awareness, digital content creation in Tamil, and curriculum reforms to ensure a balanced coexistence of innovation and tradition in linguistic practices.